Sesamin ameliorates nonalcoholic steatohepatitis through inhibiting hepatocyte pyroptosis in vivo and in vitro - Zhang, Teng; Zhou, Yong; Zhang, Yan; Wang, De-Guo; Lv, Qiu-Yue; Wang, Wen; Bai, Ya-Ping; Hua, Qiang; Guo, Li-Qun (Frontiers in Pharmacology, 2024)
Sesamin (Ses) is a natural lignan abundantly present in sesame and sesame oil. Pyroptosis, a newly identified type of pro-inflammatory programmed necrosis, contributes to the development of non-alcoholic steatohepatitis (NASH) when hepatocyte pyroptosis is excessive. In this study, Ses treatment demonstrated an improvement in hepatic damage in mice with high-fat, high-cholesterol diet-induced NASH and palmitate (PA)-treated mouse primary hepatocytes. Notably, we discovered, for the first time, that Ses could alleviate hepatocyte pyroptosis both in vivo and in vitro. Furthermore, treatment with phorbol myristate acetate, a protein kinase Cδ (PKCδ) agonist, increased PKCδ phosphorylation and attenuated the protective effects of Ses against pyroptosis in PA-treated mouse primary hepatocytes. Mechanistically, Ses treatment alleviated hepatocyte pyroptosis in NASH, which was associated with the regulation of the PKCδ/nod-like receptor family CARD domain-containing protein 4/caspase-1 axis. This study introduces a novel concept and target, suggesting the potential use of functional factors in food to alleviate liver damage caused by NASH.